"Let me through, I'm a doctor!" : professional socialization in the transition from education to work - Lindberg, Ola, 1979- (Umeå : Pedagogiska institutionen, Umeå universitet, 2012)
Med sammanfattning på svenska.
Härtill 4 uppsatser.
Doktorsavhandling
Keywords: Employablility; Medical education; koulutus; työelämä; käyttäytymistieteet; lääkärit; utbildning; arbetsliv; beteendevetenskaper; läkare